On the Margins, Getting By, Persevering, or Flying High? The Intersection of Wellbeing, Attainment, and Transitions in a Scottish Longitudinal Study - Dunlop, Aline-Wendy (Frontiers in Education, 2021)
Responding to the question What aspects of the intersection of wellbeing, attainment and school transitions help to explain school leaving outcomes? this paper focuses on the variability of a sample of focal children’s wellbeing and attainment trajectories on the journey through education from the age of 3 to school leaving at 16 -18 years old in one Scottish Council area. The relationships between wellbeing and attainment either side of primary and secondary school start are explored and the ways these may link to transition experiences and educational outcomes at school leaving are considered. A new interpretation of Bronfenbrenner’s ‘mature’ bioecological system model which considers the person, processes and educational contexts that children travel through over time frames the methodology, methods and findings of a data rich exploratory-interpretive longitudinal study and discusses their relationship to current dilemmas surrounding educational outcomes in Scotland at the present time. The role of wellbeing and attainment measures as proxies for school success is considered and found to be too narrow a concept in the form experienced by the focal group of study participants. While wellbeing needs to be much more clearly defined and fostered, concepts of attainment predicated only on maths and literacy (and on some measures, science) are found to be insufficient in that they discriminate against too many. Attention to the opportunities offered and risks inherent in periods of educational transition allow identification of, and reflection upon the qualities of a good educational transition from both early childhood education to school start, and subsequently in the move to secondary education. It is found that a ‘good transition’ though it exists, is not available to all children: consequently more equitable approaches are advocated, and alternatives for practical and policy action are proposed. Study of educational transitions dates back fifty years: is it not time for systems themselves to change?